The Revolutionary War : an interactive history adventure - Raum, Elizabeth (Capstone Press, 2010)
Describes the events of the American Revolutionary War and explains the significance of the war today. The reader's choices reveal the historical details from the perspective of a young girl, a patriot fighter, and a loyalist determined to keep America under British rule.